2015
DOI: 10.1186/s13058-015-0545-8
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic functions of the tumor- and metastasis-suppressing matrix metalloproteinase-8 in mammary cancer in MMTV-PyMT transgenic mice

Abstract: IntroductionMatrix metalloproteinase-8 (MMP-8; neutrophil collagenase) is an important regulator of innate immunity that has oncosuppressive actions in numerous tumor types.MethodsWe have intercrossed Mmp8-null mice with the Polyoma virus middle T oncogene-driven (MMTV-PyMT) mouse model of mammary cancer to explore the effects of loss of MMP-8 on the incidence and progression of mammary carcinomas.ResultsIn this aggressive mouse model of breast cancer, loss of MMP-8 accelerated tumor onset even further, such t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 56 publications
2
32
0
2
Order By: Relevance
“…The salivary MMP-8 levels were highest in non-smoking women without oral HPV infection. This result is in line with the earlier observations indicating the protective role of MMP-8 [22][23][24][25][26][27][28][29]. Based on this study, however, it cannot be concluded whether a low salivary MMP-8 concentration indicates a condition with an increased risk for chronic HPV infection or if the infection itself lowers MMP-8 expression.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The salivary MMP-8 levels were highest in non-smoking women without oral HPV infection. This result is in line with the earlier observations indicating the protective role of MMP-8 [22][23][24][25][26][27][28][29]. Based on this study, however, it cannot be concluded whether a low salivary MMP-8 concentration indicates a condition with an increased risk for chronic HPV infection or if the infection itself lowers MMP-8 expression.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, HPV16 E7 increases the activity of MMP-9 in vitro [21]. In contrast, MMP-8 seems to have a protective role in a variety of cancers [22][23][24][25][26] and inflammatory diseases [27][28][29]. In a population based study, MMP-8 levels were positively associated with better disease specific survival of the patients with a tongue SCC [22].…”
Section: Introductionmentioning
confidence: 99%
“…MMP-8 was identified as a tumour suppressor nearly a decade ago when the MMP-8 knock-out mouse was found to be more susceptible to skin tumuorigenesis as compared to a WT mouse [28]. There is also strong evidence for a role in tumour prevention in breast cancer, melanoma and squamous cell carcinoma [22, 26, 28, 29, 31, 32, 5659]. Particularly in melanoma; MMP-8 is frequently mutated by loss of heterozygosity (LOH), which is a hallmark for tumour-suppressor proteins [22].…”
Section: Discussionmentioning
confidence: 99%
“…Since it was first reported that MMP-8 -/- mice exhibit increased incidence of skin tumours when challenged with chemical carcinogenesis, MMP-8 has been demonstrated to exert a clear tumour-suppressor function [22, 26, 28, 29]. There is a growing body of evidence accumulating that MMP-8 has an anticancer role in breast cancer, malignant melanoma and tongue squamous cell carcinoma, [22, 26, 28, 3032]. Interestingly, identification of non-structural substrates of MMP-8 [28, 3337], suggests that the biological function of MMP-8 is much more complicated than just Col-I degradation.…”
Section: Introductionmentioning
confidence: 99%
“…MMP-8 provides one of the more clear-cut examples of this phenomenon. In mouse models of breast cancer, high expression of MMP-8 suppresses metastasis, while MMP-8 silencing or knockout promotes tumor progression and metastasis [Montel et al 2004; Decock et al 2015]. Importantly, the net antitumor effect of MMP-8 is corroborated by the association of MMP-8 tumor expression with longer relapse-free survival in breast cancer patients [Gutiérrez-Fernández et al 2008], and by the association of a high expression promoter variant of the MMP-8 gene with more favorable prognosis [Decock et al 2007].…”
Section: Clinical Studies Identify Specific Mmps As Most Likely Theramentioning
confidence: 99%